Inovasi Pembuatan Pasta Ravioli Isi Ayam dengan Proporsi Tepung Mocaf dan Tepung Tempe Terhadap Karakteristik Sensori dan PreferensiInovasi Pembuatan Pasta Ravioli Isi Ayam dengan Proporsi Tepung Mocaf dan Tepung Tempe Terhadap Karakteristik Sensori dan Preferensi - Shayla Davinia Ikhsani; Any Sutiadiningsih; Mauren Gitta Miranti; Aisyah Nurin Kamilya (Indo-MathEdu Intellectuals Journal, 2026)
This study was motivated by the high dependence on wheat flour in pasta products, making it necessary to utilize local food ingredients as an alternative. This study aimed to examine the sensory characteristics, consumer preference level, and best formulation of chicken-filled ravioli pasta using mocaf flour and tempe flour in different proportions. The method used was experimental research with three treatments, namely 90% mocaf flour and 10% tempe flour, 80% mocaf flour and 20% tempe flour, and 70% mocaf flour and 30% tempe flour. Data were collected through sensory evaluation covering color, taste, texture, and overall liking by panelists. The data were analyzed using the Friedman test to determine differences among treatments, followed by the Wilcoxon test to identify the best formulation. The results showed that differences in the proportions of mocaf flour and tempe flour produced significant differences in color and overall liking, but did not show significant differences in taste and texture. The formulation with 70% mocaf flour and 30% tempe flour obtained the highest mean scores in most sensory attributes and was the most preferred by panelists. Therefore, this formulation was identified as the best product in this study. The implications of this study indicate that a combination of mocaf flour and tempe flour has the potential to be used as an alternative raw material in the development of local food-based pasta with good sensory characteristics and a high level of consumer acceptance